2022
DOI: 10.1177/00219983211066389
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the mechanical behavior and damage of 3D printed composites under three-point bending

Abstract: Three-dimensional (3D) printing has been triumphantly applied for the manufacture of various composite components. In this work, acoustic emission (AE), X-ray micro-computed tomography (Micro-CT) are used in conjunction with digital image correlation (DIC) measurement to investigate the mechanical behaviors of 3D printed continuous fiber reinforced composites under three-point bending test. Meanwhile, several mechanical experiments are carried out to study the flexural properties of three kinds of composite sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Ren et al 26 investigated the phenomenon of surface delamination in the bending process of carbon fiber composites, recorded the damage by AE, identified the damage types by cluster analysis, and verified the damage by micro‐CT, which can realize health monitoring of the composite structure. Ma et al 27 examined the behavior of 3D printed continuous fiber reinforced composites during bending. They used digital image correlation (DIC), AE and CT, to obtain information on the bending properties, damage process and distribution, key damage and delamination mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al 26 investigated the phenomenon of surface delamination in the bending process of carbon fiber composites, recorded the damage by AE, identified the damage types by cluster analysis, and verified the damage by micro‐CT, which can realize health monitoring of the composite structure. Ma et al 27 examined the behavior of 3D printed continuous fiber reinforced composites during bending. They used digital image correlation (DIC), AE and CT, to obtain information on the bending properties, damage process and distribution, key damage and delamination mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…They used AE waveforms associated with different damage modes, i.e., matrix cracking, delamination, debonding, and fiber breakage. Recently, Ma et al [7] used AE and X-ray micro-computed tomography in conjunction with digital image correlation measurements to investigate the mechanical behavior of 3D printed continuous fiber-reinforced composites in three-point bending. They ascertained that parameters such as frequency, amplitude, and amplitude ratio were closely associated with the damage process of different specimens using the crossvalidation results of cluster analysis (k-means), K-Nearest Neighbor and principal component analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the torsional AE analyzed signals had good agreement with the FCM classi cations. Other than this, the k-means clustering method can also be used to precisely analyze the AE results by easily identifying the different cluster zones [21].…”
Section: Introductionmentioning
confidence: 99%